Non-Invasive Brain Stimulation Enhances the Effects of Melodic Intonation Therapy - Vines, Bradley W.; Norton, Andrea C.; Schlaug, Gottfried (Frontiers in Psychology, 2011)
Research has suggested that a fronto-temporal network in the right hemisphere may be responsible for mediating Melodic Intonation Therapy’s positive effects on speech recovery. We investigated the potential for a non-invasive brain stimulation technique, transcranial direct current stimulation (tDCS), to augment the benefits of MIT in patients with non-fluent aphasia by modulating neural activity in the brain during treatment with MIT. The polarity of the current applied to the scalp determines the effects of tDCS on the underlying tissue: anodal tDCS increases excitability, whereas cathodal tDCS decreases excitability. We applied anodal tDCS to the posterior inferior frontal gyrus (IFG) of the right hemisphere, an area that has been shown to both contribute to singing through the mapping of sounds to ariculatory actions and serve as a key region in the process of recovery from aphasia, particularly in patients with large left hemispheric lesions. The stimulation was applied while patients were treated with MIT by a trained therapist. Six patients with moderate to severe non-fluent aphasia underwent three consecutive days of anodal-tDCS+MIT, and an equivalent series of sham-tDCS+MIT. The two treatment series were separated by one week, and the order in which the treatments were administered was randomized. Compared to the effects of sham-tDCS+MIT, anodal-tDCS+MIT led to significant improvements in fluency of speech. These results support the hypothesis that, as the brain seeks to reorganize and compensate for damage to left-hemisphere language centers, combining anodal-tDCS with MIT may further recovery from post-stroke aphasia by enhancing activity in a right-hemisphere sensorimotor network for articulation.